2022
DOI: 10.1371/journal.pone.0265329
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene pottery production and exchange: Provenance studies of hunter-gatherer wares from southern Kyushu, Japan by neutron activation analysis

Abstract: Late Pleistocene hunter-gatherers in East Asia adopted pottery, yet the ability to reconstruct circulation, mobility, and exchange has been hampered, in part, due to problematic regional geochronology. The driving forces behind pottery adoption is unclear. The purpose of this study is to test our results of the first systematic petrographic pottery sourcing from the pre-Younger Dryas by utilizing neutron activation analysis. We examine samples from the Sankauyama I site on Tanegashima Island, southern Japan, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Recent archaeological research has demonstrated that the earliest pottery was already being produced by communities of hunter-gatherers in Asia (Chi 2002;Kuzmin 2002;2010;Bougard 2003;Keally et al 2004;Kuzmin, Vetrov 2007;Boaretto et al 2009;Wu et al 2012;Craig et al 2013;Budja 2016;Iizuka et al 2022a;2022b;Nakazawa et al 2022). Analysis of pottery dated to the very end of the Upper Palaeolithic has established that vessels discovered in Japan and Russia contain organic inclusions, deliberately added to the mixture, while the presence of quartzite -and occasionally also grog, or crushed recycled pottery -has been detected in pottery pastes from various parts of China (Chi 2002: 32-33;Keally et al 2004: 349).…”
Section: Introduction Clay Objects Containing Inclusions and Their Ch...mentioning
confidence: 99%
“…Recent archaeological research has demonstrated that the earliest pottery was already being produced by communities of hunter-gatherers in Asia (Chi 2002;Kuzmin 2002;2010;Bougard 2003;Keally et al 2004;Kuzmin, Vetrov 2007;Boaretto et al 2009;Wu et al 2012;Craig et al 2013;Budja 2016;Iizuka et al 2022a;2022b;Nakazawa et al 2022). Analysis of pottery dated to the very end of the Upper Palaeolithic has established that vessels discovered in Japan and Russia contain organic inclusions, deliberately added to the mixture, while the presence of quartzite -and occasionally also grog, or crushed recycled pottery -has been detected in pottery pastes from various parts of China (Chi 2002: 32-33;Keally et al 2004: 349).…”
Section: Introduction Clay Objects Containing Inclusions and Their Ch...mentioning
confidence: 99%